2019
DOI: 10.1111/jpn.13229
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term peroral administration of bitter apricot seeds influences cortical bone microstructure of rabbits

Abstract: Apricot seeds due to the presence of cyanogenic glycoside amygdalin belong to the popular “alternative cancer cures", although anticancer effect of amygdalin remains controversial. This in vivo study points to the effect of long‐term peroral administration of bitter apricot seeds on bone microstructure of rabbits since chronic amygdalin toxicity in relation to bone parameters has not been investigated yet. Rabbits (n = 16) were randomly divided into four experimental groups of 4 animals each. Three experimenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 51 publications
1
0
0
Order By: Relevance
“…The male rats’ body weight obtained data run in consistent with the previous studies which reported a marked reduction in body weight of rats treated with AlCl 3 (Yang et al, 2020 ; Buraimoh & Ojo, 2014 ; Justin-Thenmozhi et al, 2018 ). The reduced body weight as a result of AMG+AlCl 3 and AMGLN+AlCl 3 oral gavage may be attributed to AlCl 3 toxicity besides absence of negative effect of them on body weight which run in agreement with (Dogru et al, 2017 ; Kovacova et al, 2020 ). However, the ability of SP+AlCl 3 and SPLN+AlCl 3 to ameliorate the weight loss induced by AlCl 3 may be attributed to its content of highly digestible nutrients, vitamins, and minerals as previously reported by (Barkallah et al, 2020 ; Fouda & Ismail, 2017 ; Farag et al, 2016 ).…”
Section: Discussionsupporting
confidence: 80%
“…The male rats’ body weight obtained data run in consistent with the previous studies which reported a marked reduction in body weight of rats treated with AlCl 3 (Yang et al, 2020 ; Buraimoh & Ojo, 2014 ; Justin-Thenmozhi et al, 2018 ). The reduced body weight as a result of AMG+AlCl 3 and AMGLN+AlCl 3 oral gavage may be attributed to AlCl 3 toxicity besides absence of negative effect of them on body weight which run in agreement with (Dogru et al, 2017 ; Kovacova et al, 2020 ). However, the ability of SP+AlCl 3 and SPLN+AlCl 3 to ameliorate the weight loss induced by AlCl 3 may be attributed to its content of highly digestible nutrients, vitamins, and minerals as previously reported by (Barkallah et al, 2020 ; Fouda & Ismail, 2017 ; Farag et al, 2016 ).…”
Section: Discussionsupporting
confidence: 80%